A multifunctional nanoplatform based on mesoporous silica nanoparticles for imaging-guided chemo/photodynamic synergetic therapy. Issue 49 (16th June 2017) - Liu, Yadan; Liu, Xiaolin; Xiao, Yue; Chen, Fangman; Xiao, Fangnan
Abstract : A multifunctional nanoplatform, MSN@C-dots/RB, is fabricated for drug delivery and imaging-guided chemo/photodynamic synergistic therapy. Abstract : Multifunctional nanoplatforms based on mesoporous silica nanoparticles (MSNs) have recently shown great promise in drug delivery and therapy. Herein, a multifunctional nanoplatform based on MSNs is fabricated by a modified micro-emulsion method for drug delivery and imaging-guided chemo/photodynamic synergistic therapy. Carbon dots (C-dots) and a photosensitizer, rose bengal (RB), are embedded in the core/shell structured MSNs to form MSN@C-dots/RB nanoparticles, in which C-dots can serve as a fluorescence probe to achieve cell fluorescence imaging and RB can generate singlet oxygen to perform photodynamic therapy. MSN@C-dots/RB nanoparticles can efficiently prevent the self-aggregation-induced quenching of photosensitizer molecules, which facilitates a large production of cytotoxic singlet oxygen and thus an enhanced PDT efficacy. Furthermore, a remarkable chemo/photodynamic synergistic anti-tumor effect was achieved with MSN@C-dots/RB nanoparticles loaded with doxorubicin (DOX) under green light irradiation. In addition, a significant bacterial inhibitory effect has been achieved by the antimicrobial assay via loading ampicillin in the MSNs@C-dots/RB nanoparticles, thereby demonstrating the versatility of this multifunctional nanoplatform. The results revealed that this MSN-based chemo/photodynamic synergistic nanoplatform has great promise in imaging assisted cancer therapy and bacteria inhibition.